An Advanced Technique for Linear Low‐Density Polyethylene Composition Determination: TGA–IST16–GC–MS Coupling. Issue 17 (12th August 2019) - Boyron, Olivier; Marre, Tiffany; Delauzun, Alain; Cozic, Ronan; Boisson, Christophe
Abstract: An innovative method based on thermogravimetric analysis combined with gas chromatography and mass spectrometry, TGA–IST16–GC–MS, is developed for measuring the comonomer type and the comonomer content in a series of linear low‐density polyethylenes (LLDPE). LLDPE such as copolymers of ethylene and octene or ethylene and hexene are synthetized using the Et(Ind)2 ZrCl2 zirconium‐metallocene catalyst. Their characterization with TGA‐IST16‐GC‐MS system is compared to one of the polyethylenes prepared under similar conditions and used as reference. TGA‐IST16‐GC‐MS allows discriminating the comonomer type (hexene or octene) and content. Combining the versatility of thermal analysis and the accuracy and sensitivity of mass spectrometry, this original method proves to be very useful for routine characterization of LLDPE. It has the advantage of being quicker and more easily performed that traditional means of obtaining copolymer compositions such as nuclear magnetic resonance, or through separation techniques such as temperature rising elution fractionation (TREF). Abstract : An innovative technique, TGA‐IST16‐GC‐MS, thermogravimetric analysis combined with gas chromatography and mass spectrometry, is used to characterize linear low‐density polyethylenes (LLDPE). The IST16 interface collects the gases produced during the degradation of the copolymer before GC‐MS analysis. A specific signature of the comonomer present in LLDPE is identified and used for quantitative analysis of comonomer content.